A Graphene Based Bandwidth Enhanced Metamaterial Absorber using Circular Ring - Ghosh S.K.; Yadav V.S.; Bhattacharyya S.; Das S. (My University, 2025)
A thin ( λ/8) bandwidth-enhanced metamaterial absorber has been presented in this paper where the unit cell contains single circular ring. The geometric parameters of the graphene-embedded structure are controlled in such a way that the absorber should exhibit bandwidth-enhanced absorption between 42.5 THz and 65 THz. Three distinct absorption peaks are obtained at 46.872 THz, 53.374 THz, and 61.035 THz with respective absorptivity of 99.9%, 98.4% and 80%. The proposed structure has been investigated under oblique incidences for both TE and TM polarizations where bandwidth enhanced absorption has been observed up to 50° incident angles for both cases. Furthermore, the graphene embedded structure exhibits polarization insensitive bandwidth-enhanced absorption. © 2018 IEEE.